"I'm a Survivor": Aboriginal and Torres Strait Islander Cancer Survivors' Perspectives of Cancer Survivorship. Issue 2 (March 2020) - Meiklejohn, Judith A.; Bailie, Ross; Adams, Jon; Garvey, Gail; Bernardes, Christina M.; Williamson, Daniel; Marcusson, Beverly; Arley, Brian; Martin, Jennifer H.; Walpole, Euan T.; Valery, Patricia C.
Abstract : Background: Disparity in outcomes between Indigenous and non-Indigenous people after cancer diagnosis is multifactorial, including lower cancer screening participation, later diagnosis, reduced access and uptake of cancer treatment, higher rate of comorbidities, and barriers accessing the health system. Little is known about cancer survivorship experiences. Objective: The aim of this study was to explore Indigenous Australian cancer survivor's perspectives of cancer survivorship. Methods: Indigenous people who completed cancer treatment 6 months to 5 years before fieldwork were recruited from a tertiary hospital and remote primary health service for this qualitative study. Data collection was guided by yarning methods, a culturally appropriate method emphasizing storytelling. Data were interpreted using a social constructionist framework. Results: Thirteen women and 6 men were interviewed. Participants' past experiences contributed to their specific identity as survivors. Participants described factors affecting a positive transition from cancer patient to cancer survivor and the importance of ongoing family support in helping to manage survivorship. Finally, participants described a range of community support they received and provided to others and how this improved their cancer survivorship. Conclusion: Although a range of experiences are presented, this study provides evidence that the survivorship perspectives of Indigenous cancer survivors may be, in part, shared by non-Indigenous cancer survivors. Implications for Practice: Acknowledging Indigenous cancer survivors' past experiences and how these influence their overall well-being is important for providing patient-centered and culturally appropriate care. Nurses and other healthcare professionals may use this knowledge to foster a range of coping strategies to assist Indigenous cancer survivors to live well.